E-Libwork Web Portal Design as a Digital Learning Resources - Silvana, Hana; Rullyana, Gema; Agustina, Susanti; Ardiansah, Ardiansah (Universitas Pendidikan Indonesia, 2021)
The purpose of this research is to design e-LibWork as a digital instructional resources that can improve student’s information management skills. The application and development of Information and Communication Technology (ICT) -based learning is one of the most strategic steps in facing a better future for Indonesian education. Future learning is not just following global trends but is a strategic step in an effort to improve access and quality of education services to the public. The Library and Information Science Study Program develops its students to prepare graduate students to develop their abilities and competencies to find, manage, and evaluate information and knowledge, therefore in this effort it must improve access and quality of educational services, one of which is developing digital instructional resources as one of them. one source of learning. The method in this research is a method that usesDesign and Development (DnD). The subjects of this study consisted of several experts and participants. Experts in web design development consist of 1 web practitioner, and 1 content expert about learning resources. The implementation phase involved 32 participants for the pilot process.